2001
DOI: 10.1038/sj.onc.1204172
|View full text |Cite
|
Sign up to set email alerts
|

p53-dependent radiation-induced crypt intestinal epithelial cells apoptosis is mediated in part through TNF-TNFR1 system

Abstract: Radiation induces apoptosis of crypt intestinal epithelial cells (IEC) through a pathway that is largely dependent on p53. However, exactly how p53 mediates IEC apoptosis is unclear. Studies in vitro suggest that one mechanism by which p53 mediates apoptosis is through its ability to transactivate members of the TNF receptor family of`Death Receptors'. Here, we examined the role of one of its member, TNF receptor type 1 (TNFR1), in an in vivo model of p53-dependent radiation-induced IEC apoptosis. We demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…We performed RNase protection assays on primary IEC and found constitutive expression of TNFR1 (p55) (Fig. 1C), consistent with a previous observation of TNFR1 protein on the surface of IEC (19). Because TNF␣ is produced by activated lymphocytes infiltrating the small intestine (20), we investigated the possibility that TNF␣ acts through the TNFR1 on IEC to induce Fas-ligand in IEC following SEB-induced activation of peripheral lymphocytes.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…We performed RNase protection assays on primary IEC and found constitutive expression of TNFR1 (p55) (Fig. 1C), consistent with a previous observation of TNFR1 protein on the surface of IEC (19). Because TNF␣ is produced by activated lymphocytes infiltrating the small intestine (20), we investigated the possibility that TNF␣ acts through the TNFR1 on IEC to induce Fas-ligand in IEC following SEB-induced activation of peripheral lymphocytes.…”
Section: Resultsmentioning
confidence: 50%
“…5). IEC express TNFR1 (19), and animals lacking TNFR1 are similarly resistant to induction of IEC Fas-ligand expression following SEB injection.…”
Section: Resultsmentioning
confidence: 99%
“…Key factors in NEC pathogenesis, such as hypoxia reoxygenation, PAF, TNF-␣, and endotoxin, have been shown to increase mucosal permeability (17)(18)(19)(20)(21). Most of these mediators have been shown to cause apoptosis of intestinal epithelial cells as well (22)(23)(24), but the connection between apoptosis and subsequent gross morphologic damage in NEC is yet to be elucidated.…”
mentioning
confidence: 99%
“…Hence, it is possible that sublethal irradiation may enhance the effect of GVHD through its effect on host APC, a population that is relatively resistant to radiationinduced apoptosis. We have shown that sublethal radiation induces the systemic production of numerous proinflammatory cytokines such as TNF (40), which is primarily produced by APC, and this induction is attenuated in the p53 Ϫ/Ϫ mice. Hence, it is plausible that radiation induces an initial critical inflammatory response through its effect on p53, and this is further propagated by the injection of parental cells recognizing alloantigen in a concept commonly regarded as cytokine storm (41).…”
Section: Discussionmentioning
confidence: 99%